2004
DOI: 10.1100/tsw.2004.114
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium, Aging, and the Elderly Patient

Abstract: Magnesium, beyond any doubt, plays an important role in metabolism. Alterations of magnesium levels have an impact on many organs and systems, especially during aging. We had 156 participants aged 60–93 years (average 74.7 years) in our survey. Of them, 49 were men and 107 were women. Treatment with loop diuretics (Furosemid and Bumetanide) and magnesium levels was correlated, as well as the influence of magnesium levels on life span. Serum magnesium levels were measured in patients receiving diuretics and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…It has been suggested that low serum Mg level could be a marker of insulin resistance [9]. Not only is hypomagnesemia more prevalent in elderly subjects but the effects of changes in Mg levels are also more prominent in this age group [11,12].…”
mentioning
confidence: 99%
“…It has been suggested that low serum Mg level could be a marker of insulin resistance [9]. Not only is hypomagnesemia more prevalent in elderly subjects but the effects of changes in Mg levels are also more prominent in this age group [11,12].…”
mentioning
confidence: 99%
“…Aging represents a major risk factor for magnesium (Mg) deficit. Several alterations of Mg status have been identified in the elderly [1][2][3][4][5][6][7][8][9][10][11][12][13]. Total body Mg content tends to decrease with age, with bone being the main storage compartment of body Mg. Of the 21-28 g of Mg present in the adult human body, about 55-65% is in the mineral phase in the skeleton, 34-44% in the intracellular space, and only 1% in the extracellular fluid [14].…”
mentioning
confidence: 99%
“…In particular, in healthy elderly (N65 years old) the levels of Mg-ions and intracellular free Mg are reduced with respect to young controls (b 65 years old), while the total serum Mg remained unchanged (Barbagallo et al, 2000(Barbagallo et al, , 2009. Many studies reported the same observation of unaltered values of Mg during aging (Davidovic et al, 2004;Del Corso et al, 2000;Mataix et al, 2006). In the study of Sfar et al (2012) Mg mean concentrations did not show any significant variation relatively to age (30-60 years, 20.51 μg/ml; 65-85 years: 20.86 μg/ml).…”
Section: Magnesiummentioning
confidence: 76%
“…The Mg deficiency can cause oxidative damage and peroxidation, insulin resistance, disordered Mg metabolism in the bones, adrenaline hyperactivity and illness (diabetes, for example). In addition, Mg deficiency influences the DNA repair, lead to genetic instability and accelerated aging, affects different cell functions and initiates stress-induced premature senescence (Davidovic et al, 2004;Killilea and Maier, 2008). Manganese is indispensable for normal development and body functions of all mammals.…”
Section: Introductionmentioning
confidence: 98%